1992
DOI: 10.1073/pnas.89.15.7282
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p70s6k is associated with phosphorylation of four clustered sites displaying Ser/Thr-Pro motifs.

Abstract: Partial amino acid sequences were obtained from 22 internal tryptic peptides of rat liver p70' (Mr 70000 ribosomal protein S6 kinase), 3 of which were found to contain phosphorylated residues. To determine whether these sites were asoated with p70" activation, the kinase was labeled to high specific activity with 32P1 in Swiss mouse 3T3 cells. By sequential cleavage with CNBr and endoproteinase Lys-C followed by two-dimensonal tryptic peptide analysis, it could be shown that all of the sites were located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
128
2
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 52 publications
1
128
2
2
Order By: Relevance
“…We have investigated the contribution of these pathways to the di erentiation process by the use of chemical inhibitors. P70S6K was inhibited with the immunosuppressant rapamycin (Ferrari et al, 1992). To inhibit the a and b isoforms of p38-MAPK we used the pyridinyl imidazole compound PD169316 (PD*) (Kummer et al, 1997).…”
Section: Insulin (In the Presence Of Pd) Produces C2ras Myotubes In Amentioning
confidence: 99%
“…We have investigated the contribution of these pathways to the di erentiation process by the use of chemical inhibitors. P70S6K was inhibited with the immunosuppressant rapamycin (Ferrari et al, 1992). To inhibit the a and b isoforms of p38-MAPK we used the pyridinyl imidazole compound PD169316 (PD*) (Kummer et al, 1997).…”
Section: Insulin (In the Presence Of Pd) Produces C2ras Myotubes In Amentioning
confidence: 99%
“…In parallel it has been demonstrated that the immunosuppressant rapamycin, a bacterial macrolide, negates mitogen-induced activation of p70 s6k by preventing the acute phosphorylation of a specific subset of sites, including T 229 , T 389 , S 404 , and S 411 (54). These sites were found to be flanked by large aromatic residues, with the exception of S 411 , which exhibits an S/TP motif, as do the remaining three unaffected phosphorylation sites (18,54). Of the rapamycin-sensitive sites, the principal site of rapamycin-induced dephosphorylation leading to p70 s6k inactivation was identified as T 389 , which resides in the linker region, coupling the catalytic and autoinhibitory domains (54).…”
mentioning
confidence: 99%
“…Furthermore, incubation of p70 S6K with synthetic peptides derived from this homologous region substantially hinders its activation (68, 69) demonstrating that this module, in the context of the full-length p70 S6K polypeptide, may serve an autoinhibitory function. Stimulation of cells in culture with growth factors initiates signals that lead to the hierarchical activation of p70 S6K, commencing with the (Ser/Thr)Pro-specific phosphorylation of a cluster of 4 -6 residues with the carboxyl terminus of the kinase (19). This battery of phosphorylations promotes a conformational change that relieves autoinhibition imposed by the carboxyl terminus and, in addition, exposes additional phosphorylation sites initially buried within interior of p70 S6K.…”
Section: Transcriptional Scenarios Involved In Regulation Of P70 S6kmentioning
confidence: 99%
“…Two key observations support this premise. First, the primary amino acid sequence surrounding the cluster of p70 S6K carboxyl-terminal phosphorylation sites exhibits strong homology to the region within its substrate, S6, that it phosphorylates (19,68); hence, the designation "pseudosubstrate" domain. Furthermore, incubation of p70 S6K with synthetic peptides derived from this homologous region substantially hinders its activation (68, 69) demonstrating that this module, in the context of the full-length p70 S6K polypeptide, may serve an autoinhibitory function.…”
Section: Transcriptional Scenarios Involved In Regulation Of P70 S6kmentioning
confidence: 99%
See 1 more Smart Citation